2023
DOI: 10.3390/cells12081182
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptome Analysis Revealed Heterogeneity and Identified Novel Therapeutic Targets for Breast Cancer Subtypes

Abstract: Breast cancer (BC) is a heterogeneous disease, which is primarily classified according to hormone receptors and HER2 expression. Despite the many advances in BC diagnosis and management, the identification of novel actionable therapeutic targets expressed by cancerous cells has always been a daunting task due to the large heterogeneity of the disease and the presence of non-cancerous cells (i.e., immune cells and stromal cells) within the tumor microenvironment. In the current study, we employed computational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
(50 reference statements)
2
3
0
Order By: Relevance
“…The poor prognostic effect is observed in advanced (Stage 3) disease, and is present in HER-2 positive and triple negative breast cancers. Our data agrees with previous recent studies showing an association of high ENO1 expression with the aggressive basal subtype and a favourable prognosis in patients with early stage breast cancer but not with advanced stage disease and/or basal breast cancer [16,26,38]. We also observed that methylation of the gene is associated with a good prognostic effect, consistent with the expected effect from reducing ENO1 gene expression.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The poor prognostic effect is observed in advanced (Stage 3) disease, and is present in HER-2 positive and triple negative breast cancers. Our data agrees with previous recent studies showing an association of high ENO1 expression with the aggressive basal subtype and a favourable prognosis in patients with early stage breast cancer but not with advanced stage disease and/or basal breast cancer [16,26,38]. We also observed that methylation of the gene is associated with a good prognostic effect, consistent with the expected effect from reducing ENO1 gene expression.…”
Section: Discussionsupporting
confidence: 93%
“…In breast cancer, it’s been shown in vitro that silencing ENO1 inhibits the proliferation, migration and invasion of breast cancer cells [24] and in a xenograft mouse model, inhibition of ENO1 expression increased tolerance to hypoxia in tumour cells, showing also slow reduced tumour size, cell growth and increased apoptosis [25]. A recent, single-cell transcriptomic profiling of breast cancer patients, identified higher ENO1 expression in the aggressive basal subtype, compared to hormone-and/or HER2-positive subtypes and this overexpression was linked to worse relapse-free survival [26]. They also showed that depletion of ENO1 in triple-negative breast cancer cell lines halted cell proliferation, colony formation and tumour growths (3D-organoids) and increased cell death suggesting that ENO1 could be used as a therapeutic target in this aggressive subtype [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5a). Consistent with this subtype specificity of transcriptional programs, previous studies show that both transcriptome and epigenome landscapes are distinct between ER+ and ERpatients 89,90 , single cell RNA-seq reveals transcriptome diversity between different subtypes of breast cancer 91 , and risk loci identified in GWAS show specificity between ER+ and ERpatients 8 . To examine enhancer specificity in different breast cancer molecular subtypes, we repeated the single-cell CRISPRi screen targeting the same genomic regions in (ER-) MDA-MB-231 (Fig.…”
Section: Identifying Variant-associated Enhancer Network In Er-cellssupporting
confidence: 65%
“…The 3D organoid cultures were conducted as we previously described [ 21 ]. Briefly, 250,000 transfected cells were mixed with overnight thawed Matrigel (Corning cat.…”
Section: Methodsmentioning
confidence: 99%